EVALUATION OF DISSOCIATION AND THERMODYNAMIC CONSTANTS OF QUINOLINE USING POTENTIOMETRIC METHOD IN AQUEOUS AND MIXED 0RGANIC-WATER SOLVENTS (Biological Sciences - PJSIR, 2001)
The dissociation constant (pK,.) and thermodynamic parameters Gibb's free energies (G) of quinoline compound are determined by potentiometric pH titrations in aqueous solutions at 25 to 50°C and in various mixtures of water and organic solvent systems at 25°C ±  0. 1°c.It is observed that the mixed ionization constant (pK,.M) and thermodynamic ionization constant (pK,T) values of quinoline decrease with the i ncrease of temperature and concentration of organic-water solvent systems. The curve is a parabolic one. These results are discussed in terms of solvent characteristics, solvent basicity and stabilization of conjugate acid for base by hydrogen bonding interaction in hydro-organic solvent media.The values of dissociation constant are calculated by a computer programme written in GW-BASIC. From pK, values Gibb's free energies G for the respective pK, values are computed and discussed in terms of solute solvent interactions.